Global estimates of rehabilitation needs and disease burden in tracheal, bronchus, and lung cancer from 1990 to 2019 and projections to 2045 based on the global burden of disease study 2019 - Lai, Xigui; Li, Conghui; Yang, Yao; Niu, Mingyuan; Yang, Yujie; Gu, Shanshan; Hou, Weiqian; Chen, Lili; Zhu, Yi (Frontiers in Oncology, 2023)
Background The global cancer burden is substantial and spiraling. Although rehabilitation specialists could offer assistance, oncologic rehabilitation is still underutilized and not a routine part of clinical oncology guidelines worldwide. Global investigations of disease prevalence and years lived with disability (YLDs) for tracheal, bronchus, and lung (TBL) cancer are valuable for facilitating clinical practice improvement and health resource management. The objective of this study is to report the global estimates of rehabilitation needs and disease burden of TBL cancers from 1990 to 2019 and provide predictions for 2045. Methods To estimate the need for rehabilitation, the data used from the Global Burden of Disease Study 2019 to calculate the prevalence, YLDs, and the attributable risk factors of TBL cancer. The Bayesian age-period-cohort model and Auto-Regressive Integrated Moving Average model were established to forecast the future health burden. All analyses were done at the global level and then some in the aggregation with the seven World Bank regions. All the data were analyzed by R software (x64 version 4.2.1) and Microsoft Excel (version 2019). Results Globally in 2019, 3,212,307 cases of TBL cancer (95% UI 2,937,037-3,488,346) could have benefitted from rehabilitation, contributing to 544,215 (95% UI 396,134-700,099) YLDs. Over the past 30 years, the age-standardized rate (ASR) of prevalence (EAPC = 0.51) and YLDs (EAPC = 0.03) increased. Throughout this period, the global prevalence and YLDs counts were greater in males than females. The ASR of prevalence and YLDs are projected to show a slight downward trend by 2045 on the global scale, the overall prevalence and YLDs due to TBL cancer are likely to increase further, but all indicators show a growing trend in females. Conclusion TBL cancer remains one of the major public health issues globally. According to the forecasted results, the burden of YLDs due to TBL cancer will continue to rise, and the increment is higher in females than males. A rising number of patients worldwide will benefit from rehabilitation services in the future to achieve precise control and management throughout the TBL cancer patient lifecycle.